Blood flow computational characterization inside an idealized saccular aneurysm in presence of magnetic field (2019)
The blood flow of a wide neck saccular cerebral aneurysm is modeled using numerical methods, before and after positioning a diverter flow or stent as endovascular treatment. Blood, as a magnetic fluid, is modeled computationally under the influence of different external magnetic fields. For this, a list of factors that can be varied in the external magnetic field configuration and, in turn, can affect the velocity field of the blood flow of the stented aneurysm is selected. By varying the amplitude, direction and frequency of the magnetic field, it is concluded that the amplitude has an incidence on blood velocity and shear stress in the regions where the aneurysm starts and in the stent spires. After studying the changes in blood flow, a suspension of idealized endothelial cells is computationally injected, the trajectory is modeled and the cells that are trapped on the stent spires are quantified. With this, it is possible to understand the changes in the flow conditions of the cells and to examine whether, when the blood flow is subjected to an external magnetic field, it is possible to trap endothelial cells in the region of the stent. Trapped cells finally would promote complete occlusion of the neck of the aneurysm through the stimulation of tissue growth called endothelialization.